2017
DOI: 10.1373/clinchem.2016.254672
|View full text |Cite
|
Sign up to set email alerts
|

Point: The Use of Sex-Specific Cutpoints for High-Sensitivity Cardiac Troponin Assays

Abstract: Sex-specific reference intervals for cardiac troponin exist, with the 99th percentile (the cutpoint for determination of an increased troponin) being substantially lower in females than males (1,2 ). Although recent guidelines have recommended their use (3, 4 ), clinical utilization of sex-specific ranges is limited. Troponin is engrained in our assessment of risk, diagnosis of disease, treatment options, and determination of prognosis (5 ). Irrespective of sex, the risk of acute myocardial infarction (AMI), 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…However, the current clinical evidence supporting the use of sex-specific thresholds are controversial 30 33 . There are relevant concerns regarding the use of sex-specific thresholds 34 , 35 . It is also conceivable that the clinical decision limits for myocardial infarction in different assays are not biologically equivalent 36 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the current clinical evidence supporting the use of sex-specific thresholds are controversial 30 33 . There are relevant concerns regarding the use of sex-specific thresholds 34 , 35 . It is also conceivable that the clinical decision limits for myocardial infarction in different assays are not biologically equivalent 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that sex-specific cut-offs for ruling in MI increase classification performance by increasing the specificity of the assay. [7][8][9][10] We hypothesized, based on these findings, that similar improvements in classification performance would be observed for sexspecific, rule-out cut-off concentrations, with minimal loss of sensitivity. This would potentially enable more patients to have MI ruled out with a single hs-cTnT measurement compared to currently recommended universal rule-out cut-off concentrations.…”
Section: Discussionmentioning
confidence: 92%
“…6 Sex-specific diagnostic cut-offs for high-sensitivity troponin assays have been proposed for ruling-in MI. [7][8][9][10] In the rule-in scenario, sex-specific cut-offs improve diagnostic specificity and classification performance. [7][8][9][10] We hypothesized that sex-specific rule-out cut-offs would improve the classification performance of a single hs-cTnT measurement performed at ED arrival for rapidly ruling out MI with negligible loss of sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although several reports documented a higher diagnostic accuracy of hs-cTnI when sex-specific cut-offs are used; the clinical consequences in terms of cardiovascular outcomes and mortality of using a unique hsTnI cut-off assessed by SMC technology haven’t been addressed yet ( 9 ). Thus, the clinical evaluation of a sex-specific hs-cTnI cut-off in comparison to a unique one is mandatory when this assay is used.…”
Section: Discussionmentioning
confidence: 99%